The functional analysis of quantum information theory : a collection of notes based on lectures by Gilles Pisier, K.R. Parthasarathy, Vern Paulsen and Andreas Winter /: a collection of notes based on lectures by Gilles Pisier, K.R. Parthasarathy, Vern Paulsen and Andreas Winter. (2015) - Gupta, Ved Prakash; Mandayam, Prabha; Sunder, V. S
No abstract available